Pengaruh Beban Kerja, Perceived Behavioural Control Dan Motivasi Kerja Terhadap Kinerja Pada Anggota Satlantas Polres Bukittinggi - Ramlin Manik; Dasep Suryanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2019)
Police performance is particularly concerned with the task of being one professional, objective, proportional, transparent and accountable law enforcement agency to ensure legal certainty and a sense of justice. The task carried out by the Satlantas Polres of Bukittinggi is to coordinate the execution of tasks with the agency or government agencies related to traffic vehicles and highways. Therefore, efforts are needed to improve performance through the study of various factors that are considered to affect the performance of the Bukittinggi police force itself. The research instrument used is questionnaire/questionnaire. The method of analysis used is inferential analysis with path analysis approach. Based on the results of the research and discussion that has been done, the conclusion that can be taken is (1) respondents the majority of male gender, then has a working period of between 11 – 20 years, and the majority education level graduated high school (2) The first hypothesis test results showed that the performance workload variables had a significant positive effect. (3) The second hypothesis testing results show that the Perceived Behavioural Control variable has a positive and significant influence on performance. (4) The third hypothesis testing results showed that the work motivation variables had a positive and significant influence on performance.